Singapur 2022: año de decisiones - Medina Pérez, Rafael (El Colegio de México A.C., 2023)
The following report summarizes the most important events to take place in Singapore in 2022. The research uses documentary, descriptive, and analytical evidence, and is primarily based on media reports, official documents from the Singapore government and open-access academic articles. In 2022, Singapore, after beginning to show signs of recovery from the Covid-19 pandemic, faced the inflationary and geopolitical crisis caused by Russia’s invasion of Ukraine, a situation worsened by the tensions between China and the United States over the Taiwan strait. Despite the difficulties that these events caused for Singapore’s economy, the country finished the year in a strong economic and political position, with good prospects of growth and stability for the near future.